(untitled) (Research, Society and Development, 2020)
The article presents a portfolio of publications referring to the studies about ideology in the Nonpartisan School Project based on the Methodi Ordinatio methodology. We ought to highlight that this methodology allows the researcher to state a contribution that expands the possibilities of theoretical discussions, dialoguing with themes similar to the Nonpartisan School Project. The research has characteristics of qualitative and quantitative kind, by approaching the qualitative and quantitative methods that legitimate the results found. In this respect, the methodological way required techniques of bibliographic and documentary research. The Methodi Ordinatio methodology enables the selection of articles based on the impact factor of the publication journal, the number of citations and the year of publication, which are important parameters to guide the researcher in the construction of the research. The analysis of the works showed the correlation between Nonpartisan School with an educational project aiming the maintenance of hegemony and decontextualized teaching, which strengthens the training of students who are bearers of an already determined knowledge, considered uncritical and apolitical preventing the exercise of citizenship as a social transformation. Thus, it is quoted the importance of the visibility and use of the Methodi Ordinatio methodology is repeated, that by mean of systematic review contributes significantly in the elaboration of the portfolio, remaking the trajectory of the research object.